ETHNOBOTANICAL SURVEY OF MEDICINAL PLANTS USED IN THE TREATMENT OF CANCER IN DUTSIN-MA LOCAL GOVERNMENT AREA OF KATSINA STATE, NIGERIA - Okunola, Oluwole; Ali, T.; Bello, O. M. (FUDMA Journal of Sciences, 2020)
Ethnopharmacological surveys showed that herbal remedies and their products are mostly preferred type of alternative and complementary medicine (ACM) globally. In Dutsin-Ma Local Government Area (LGA) like other places herbal remedies are popularly employed against many ailment including tumor and cancer. Therefore, this study aimed to report and document the ethnobotanical survey of the plants used in the management of tumor and cancer in Dutsin-Ma Local Government Area of Katsina State, Nigeria. Traditional medicine practitioners (TMPs) living within the area of study were cross-examined by employing questionnaires forms and key informant survey. Forty-two (42) different plant species were discovered to be employed against cancer and tumor management. The results obtained showed the parts of plant used for the herbs include; roots (4), bark (10), whole plant (13), seeds (5), fruits (3), stem (1) and leaves (6). The plant families Leguminosae caesalpinoideae and Leguminosae mimosoideae appeared more in the ethno-surveyed plant list though other families are involved. Many of these plants are mix together as storehouses for active compounds which may be good template for cancer and tumor management. The preparation of the remedies include; grinding to powder form then dispersing in either water or milk for drinking, or either mix with shear butter or water and administered on the affected part of the body. The reports showed that the herbal remedies indentified are effective for the treatment of cancer in Dutsin-Ma local government area. Hence, it is imperative for ethnobotanists and chemists to establish the toxicity and efficacy of these